2023
DOI: 10.1186/s12936-023-04548-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of dual active-ingredient bed nets on the behavioural responses of pyrethroid resistant Anopheles gambiae determined by room-scale infrared video tracking

Abstract: Background The success of insecticide treated bed nets (ITNs) for malaria vector control in Africa relies on the behaviour of various species of Anopheles. Previous research has described mosquito behavioural alterations resulting from widespread ITN coverage, which could result in a decrease in net efficacy. Here, behaviours were compared including timings of net contact, willingness to refeed and longevity post-exposure to two next-generation nets, PermaNet® 3.0 (P3 net) and Interceptor® G2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…A recent room-scale infrared video tracking study in An. gambiae s.l., testing the same net as here, also failed to find a repellent effect 51 . Similarly, when using video tracking analysis of An.…”
Section: Discussionmentioning
confidence: 53%
“…A recent room-scale infrared video tracking study in An. gambiae s.l., testing the same net as here, also failed to find a repellent effect 51 . Similarly, when using video tracking analysis of An.…”
Section: Discussionmentioning
confidence: 53%
“…from Ghana in the presence of pyrethroid resistant after LLINs mass distribution campaign. However, recent studies revealed less performance of deltamethrin-PBO net in Tanzania and Benin when compared with chorofenapyr Nets (Gleave et al, 2023). Although, non-PBO net provide protection against malaria vector; Pyrethroid-PBO performed better in enhancing less parasite prevalence via reduction in mosquito blood feeding rate and increase high mosquito mortality.…”
Section: Discussionmentioning
confidence: 97%
“…Sufficient knowledge of the entomological mode of action of ITNs already exists to enable us to identify the location of regions of the net where a number of important vector mosquito species are most likely to arrive 19 – 21 and where the insecticide is best positioned to maximise contact with mosquitoes 11 , the areas most vulnerable to physical damage that would benefit from tougher net fibre, and areas that are rarely visited by mosquitoes. Recent research suggests that most bed nets, including the new bi-treated nets, have similar entomological modes of action 22 . Can this range of knowledge not be used to design better bed nets, durable ITNs that are optimised to kill mosquitoes and prevent malaria transmission in rural Africa, rather than simply the cheapest designed products that tick the boxes required to complete a WHO form?…”
Section: Discussionmentioning
confidence: 99%